Analisis Resiliensi Pada Perempuan Korban Pelecehan Seksual di Kabupaten Jember - Rizqiana Adhe Firdaus (Psychospiritual: Journal of Trends in Islamic Psychological Research, 2025)
Sexual harassment itself refers to any form of degrading sexual behavior that can harm the individual who receives such behavior. Resilience is highly needed by individuals when facing problems and urgent situations. The aim of this study is to understand how sexual harassment occurs to women and how they defend themselves. This research uses a qualitative method, specifically a phenomenological qualitative approach. In selecting subjects, the researcher used purposive sampling technique, resulting in three subjects. Interviews, observation, and documentation were used to collect relevant data in order to obtain quality results. Furthermore, the data was validated using triangulation methods. The results of the study show that the forms of sexual harassment experienced by the subjects varied, ranging from verbal, nonverbal, to physical. These experiences had a significant impact on the victims’ psychological condition, such as the emergence of fear, excessive stress, and disruption of daily activities. However, resilience proved to play an important role in the recovery process and self-acceptance of the victims. Internal factors such as the strength of faith and zest for life became the main capital for the victims to rise and grow after the incident of sexual harassment.